Generation of socio-environmental indicators in the territorial structure of San Luis Huexotla, Texcoco, México (Agro Productividad, 2021)
Objective: This article aims to show the statistical density of the population per block, toknow its effect as a critical spatial result and its relationship with some socio-environmental indicators, this analysis-process incorporates statistical data andgeographic information systems as a model for territorial spatial analysis, which showsthe relationship between demand and generation of services.Design / Methodology / Approach: The Urban Basic Geostatistical Units data of INEGI(the Spanish acronym of the National Geostatistical Information Institute in Mexico) wasused on block-level as: number of inhabitants and number of dwellings. It wasassociated with variables identified by exploring those key stakeholders at the locality(Delegates, and the Council for Citizenship Participation (in Spanish, COPACI), as wellas the Huexotla Ejido Commissariat, their clergy representative and some other keyinformants. In addition, GIS were used to digitize vector information and to integrate arelational database for the geospatial analysis of the variables, data and indicators inorder to obtain zoning maps.Results: This study presents a proposal for the generation of socio-environmentalindicators that can be used in territorial analysis with urban and rural applications usingGeographic Information Systems as a tool.Study limitations: Transition processes converge in geographic transformation and,consequently have effects on landscape changes; demand for public services; and solidwaste generation.Findings / Conclusions: The size of the scale used for the locality analysis contributesto determine the territorial planning of a geographical space. Thus, results obtaineddeliver information for planning in the decision-making processes at localities in rural tourban transitional zones.